A Novel Intraoperative Brain Mapping Integrated Task-Presentation Platform. Issue 5 (6th February 2021) - Hameed, N U Farrukh; Zhao, Zehao; Zhang, Jie; Bu, Linghao; Zhou, Yuyao; Jin, Lei; Bai, Hongmin; Li, Weiping; Tang, Jie; Lu, Junfeng; Wu, Jinsong; Mao, Ying
Abstract: BACKGROUND: To be efficient, intraoperative task-presentation systems must accurately present various language and cognitive tasks to patients undergoing awake surgery, and record behavioral data without compromising convenience of surgery. OBJECTIVE: To present an integrated brain mapping task-presentation system we developed and evaluate its effectiveness in intraoperative task presentation. METHODS: The Brain Mapping Interactive Stimulation System (Brain MISS) is a flexible task presentation system that adjusts for patient comfort, needs of the surgeon, and operating team, with multivideo recording for patients' behavior. A total of 48 patients from 3 centers underwent intraoperative language task test during awake brain surgery with the Brain MISS. Each patient was assigned 5 questions each on picture naming, reading, and listening comprehension before and during awake surgeries. The accuracy of intraoperative stimulus-response (without electrical stimulation) was recorded. The Brain MISS was to be considered effective, if the lower limit of 95% CI of patients' intraoperative response was ≥80% and also if the accuracy of intraoperative response of all patients was statistically higher than 80%. RESULTS: All patients successfully underwent intraoperative assessment with the Brain MISS. The overall accuracy of stimulus response was 95.8% (95% CI 90.18%-100.00%), with the lower limit being higher than 80% and the response accuracy also significantly being higher than 80% in all patients ( P = .006). CONCLUSION: The Brain MISS is a portable and effective system for presenting and streamlining complicated language and cognitive tasks during awake surgery. It can also record standardized patient response data for neuroscientific research.